Scrum management approach applied in aerospace sector - Petrini, Stefano [UNESP]; Muniz, Jorge [UNESP] (My University, 2014)
The objective of this research is to describe and analyze the Scrum Agile Management Approach for an application in Products Development. The reported case relates the management of test procedure creation and its execution in the major Brazilian aircraft manufacturer. As is well known, Scrum has widely been used in management of software development as verified in numerous technical papers. However, the features present in this technique, such as, greater process visibility, flexible approach and monitoring support enable its application in distinct Product Development contexts. This research took a qualitative approach based on interviews accomplished with the Scrum team at the Test Area, focused on the Scrum implementation, its adaptation, evolution and achievements. The findings showed agility and efficiency in planning and strategic changes during the development campaign; Better visualization of the entire process for the team and subsequent areas; Increased motivation and facilitated the discussion of the performance of each member; Project goals were achieved near the projections, aided by monitoring, meetings and estimation tools. Thus, this work proposes to discuss solutions, indicate obstacles and improvements, thereby contributing to the theoretical basis of these considered themes and indicating futures updates of techniques applicable to the organization.
Keywords: Agile management; Brazilian aircraft manufacturer; Product development; Scrum; Test